THE DYNAMICS OF IMPLEMENTING THE SMALLHOLDER OIL PALM REPLANTING PROGRAM IN WEST PASAMAN REGENCY - Annisa Zara; Rahmadani Yusran (PT. Radja Intercontinental Publishing, 2026)
The Smallholder Oil Palm Replanting Program (PSR) in West Pasaman Regency is implemented amid a high demand for replanting aging smallholder oil palm plantations. However, from 2018 to 2024, the realization program accounted for only approximately 2% of the area's total smallholder plantation potential. This gap indicates that support for the program has not been fully translated into implementation achievement. This study aims to analyze the dynamics of PSR implementation in West Pasaman Regency. A qualitative descriptive approach was employed, with data collected through in-depth interviews and document analysis. Informants were purposively selected based on their involvement in program implementation and included local government officials, program facilitators, farmer group administrators, and farmers. The data were analyzed thematically and interpreted through Hill and Hupe's policy implementation perspective. The findings show that farmers' high demand for replanting, the dissemination of program information through multiple actors, and government financial support have generated strong acceptance of the program. Nevertheless, land legality issues, disparities in the institutional capacity of farmer groups, and repeated document revisions within a multi-level verification mechanism constrain farmers' ability to access the program. This study argues that policy support is a necessary but insufficient condition for implementation achievement when administrative frictions and institutional capacity gaps impede the process of translating policy acceptance into actual access to the program.